(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Objective: The objective of the study was to compare the outcome of botulinum toxin injection (BTI) and lateral internal sphincterotomy (LIS) for chronic anal fissure (CAF) in terms of efficacy and complications of both the procedures. Patients and Methods: This prospective randomized trial was conducted in the Department of Surgery; Unit II Post-Graduate Medical Institution / Lahore General Hospital, Lahore over a period of one year. One hundred and thirty adult patients with CAF were randomized to have either Botulinum toxin injection (group A) or lateral internal sphincterotomy (group B). The outcome was measured in terms of pain relief, healing rate, recurrence of fissure and procedure related complications. Patients were followed up for 6 months. Results: Majority of the patients were young with mean age of 39.35±13.24 years in group A and 35.31±12.19 years in group B. Posterior midline fissure was found in 86% and 92% of patients in group A and B respectively. At 6 months follow up, complete relief of pain was observed in 47patients (72.3%) in group A and in 62 patients (95.4%) of group B (P= 0.0008). Healing rate was superior in surgical sphincterotomy group compared to chemical sphincterotomy group (P=0.0001). Moreover, there was no significant difference in the complication rate between the groups (P=0.6976). Conclusions: Lateral internal sphincterotomy was more effective than the BTI in terms of pain relief and complete healing of CAF without any significant difference in the complication rate.